RESPONSIBILITY POLICY PEMERINTAH KABUPATEN INDRAGIRI HILIR TERHADAP ANAK JALANAN - Vivi Arfiani Siregar; Jamri; Indra Mukhlis Adnan; Muannif Ridwan (Bajang Institute, 2021)
The government's role in eradicating beggars in Indragiri Hilir Regency is primarily focused on the policies implemented by the government. The strategy is founded on a comprehensive analysis. Human life is replete with communication activities. Communication becomes critical in conveying one's thoughts, feelings, ideas, and life problems.